Management of Total Left Partial Anomalous Pulmonary Venous Connection - Pontious, Michael E; Muralidaran, Ashok; McGrath, Lidija B; Broberg, Craig; Shen, Irving; Bhamidipati, Castigliano M (Cardiology and Cardiovascular Medicine, 2021)
A 49-year-old female following transesophageal echocardiogram (TEE) to investigate an undiagnosed cardiac murmur and progressive dyspnea on exertion was found to have isolated left-sided anomalous pulmonary venous connection of all veins draining into the coronary sinus. This unique lesion required novel repair by coronary sinus unroofing and atrial septal closure.